Embbed Dajare Word Play Process in â€œShirokuma CafÃ©â€ - Salisah, Talin; Sunarni, Nani (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
Pun, in English, is a word play that is very suitable for Japanese, which has many homonyms. The name of word play in Japanese is calledÂ dajare.Â Many experts mention the types ofÂ dajare,Â and one of the researchers mentioned that there are three types ofÂ dajare.Â These three of types are homophonicÂ dajare,Â near-homophonicÂ dajare,Â andÂ embbedÂ dajare. One of the three types ofÂ dajareÂ is the main focus of research. This research explained the analysis of embbedÂ dajareÂ in an animated show titled â€œâ€œShirokuma CafÃ©â€â€, the show that has a lot ofÂ dajareÂ in conversations between Shirokuma and his friends which is seen from the vocabularies are used. The purpose of this research was to study how the embbedÂ dajareÂ word play process is used in the conversation between Shirokuma and the person he is talking to. The research method used is a descriptive qualitative method. The results of this research showed that the same or similarity of sound and form ofÂ dajareÂ does not guarantee the similarity of meaning between the referent word and the target word.